Numerical Study on the Effects of using Nanofluids in Pulsating Heat Pipe - Zufar, M.; Gunnasegaran, P.; Ching, Ng K. (International Journal of Engineering and Technology, 2018)
Pulsating Heat Pipe (PHP) is the next generation heat pipe that has a prospect in improving the heat transfer performance. The type of working fluid use in the PHP has a direct influence on the thermal performance. Incorporating nanofluid in PHP may greatly increase its thermal performance as compared to using base fluid (water). The current work focuses on the simulations of 2-dimensional flows in PHP using working fluids such as diamond, silver (Ag), silica oxide (SiO2) nanofluids and water. Constant heat flux and filling ratio of 50% were used throughout the study. From the results, it was found out that diamond nanofluid has the lowest thermal resistance value as compared to other working fluids. The effect of the number of PHP turns was studied and it was discovered that higher number of turns would produce lower thermal resistance value.